2010
DOI: 10.1021/pr901114w
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Quantifying IgG Fragments and Antigen-Binding Regions by Mass Spectrometry

Abstract: In cancer and autoimmune diseases, immunoglobulins with a specific molecular signature that could potentially be used as diagnostic or prognostic markers are released into body fluids. An immunomics approach based on this phenomenon relies on the ability to identify the specific amino acid sequences of the complementarity-determining regions (CDR) of these immunoglobulins, which in turn depends on the level of accuracy, resolution, and sensitivity that can be achieved by advanced mass spectrometry. Reproducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…6,18 A recent study into sequencing the complementarity determining regions (CDRs) of immunoglobulins by mass spectrometry opens new possibilities to study the antibody repertoire in more detail with ramifications for MScl and other autoimmune diseases. 53,54 Another interesting protein that was found at elevated levels in CSF is vitamin D-binding protein. This protein has not been described as discriminatory in other EAE model studies, but elevated levels have previously been shown in CSF from patients with secondary progressive MScl when compared to controls and patients with relapsing−remitting MScl.…”
Section: ■ Discussionmentioning
confidence: 99%
“…6,18 A recent study into sequencing the complementarity determining regions (CDRs) of immunoglobulins by mass spectrometry opens new possibilities to study the antibody repertoire in more detail with ramifications for MScl and other autoimmune diseases. 53,54 Another interesting protein that was found at elevated levels in CSF is vitamin D-binding protein. This protein has not been described as discriminatory in other EAE model studies, but elevated levels have previously been shown in CSF from patients with secondary progressive MScl when compared to controls and patients with relapsing−remitting MScl.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Based on the UV absorption of the peptides in a test chromatography run, an optimal injection volume of 15 mL was selected for nanoLC (nanoLC Ultimate 3000; Dionex, Sunnyvale, CA) separation, followed by Orbitrap MS (LTQ-Orbitrap XL ETD, Thermo Scientific, Bremen, Germany), as described before [19]. All samples were measured in a data dependent acquisition mode.…”
Section: Ltq-orbitrapmentioning
confidence: 99%
“…Sequence information of features that were identified as potential markers was manually curated after assessing homology of the sequence to known germline sequences (Spider search in Peaks), re-analysis with summed MS/MS spectra, and rejection of outlier MS/MS spectra after pairwise comparison of their similarity with R. All final amino-acid sequences of antibody group-specific features identified by Mascot database search or proposed by de novo sequencing were aligned to human immunoglobulin germline sequences using the IMGT (ImMunoGeneTics information system Ò http://www.imgt.org; Montpellier, France) database as described before [19,20]. The alignment with the most homologous germ allele was registered as provided by the IMGT tool where SmitheWaterman homology scores exceeded 35.…”
Section: Data Analysesmentioning
confidence: 99%
“…As described previously (16,17,23), we used the BLASTp search algorithm (NCBI BLAST version 2.2.22) to align the identified peptide sequences to the corresponding Ig.…”
Section: Methodsmentioning
confidence: 99%
“…Finding common characteristics of the antigen binding sites of Ig among patients might provide leads regarding the question of whether common antigenic stimuli are responsible for the recruitment of intrathecal B cells in MScl. We previously described a new approach using advanced nanoscale liquid chromatography coupled online to a high-resolution mass spectrometer (LC-MS) (10,16,17), a reliable and powerful method for the sensitive detection of CDR peptides (18). Moreover, it can also be used to compare CDR peptide profiles among a relatively large number of patients and controls.…”
mentioning
confidence: 99%